Proposed model for islamic code of ethics for directors of public listed companies / Ahmad Saiful Azlin Puteh Salin - Puteh Salin, Ahmad Saiful Azlin; Ab. Manan, Siti Khadijah; Kamaluddin, Norlela; Mohd Wahid, Siti Daleela (Research Management Institute (RMI), 2013)
This research intented to proposed a new model of Islamic code of ethics for directors of public listed companies. Several corporate scandals and collapse locally (example Transmile and Megan Media) and overseas (example Parmalat and Enron) shows that the current corporate governance and regulatory reform is unable to prevent these events from recurring. Arguably, the code of ethics for directors is under research and the current code of ethics only concentrated to bind the work of the employee of the organization as a whole, without specifically put a direct attention the the directors, the group of people that responsible for the performance of the company. Furtheremore, this code of ethics is based on the western model. Thus, the study objectives is to establish a model of code of ethics that based on Islamic principles. This study will used a semi-structured interview of several well known Islamic scholars such as Mufti to develop the model. This Islamic model will be compared and analysed with the code of ethics that based on the western model. It is expected that the outome of the research is a comprehensive model of code of ethics that based on the Islamic principles that can be applied and used by the company to construct code of ethics for their directors. This research also will highlights the differences and weaknessess of the current western model code of ethics.